2018
DOI: 10.1097/cin.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Self-tracking of Physical Activity in People With Type 2 Diabetes

Abstract: The purpose of this study was to determine the efficacy of an online self-tracking program on physical activity, glycated hemoglobin, and other health measures in patients with type 2 diabetes. Seventy-two patients with type 2 diabetes were randomly assigned to an intervention or control group. All participants received usual care. The intervention group received an activity tracker (Fitbit Zip) connected to an online lifestyle program. Physical activity was analyzed in average steps per day from week 0 until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…Most of the studies (35/37, 95%) were parallel RCTs, while two studies used a factorial design and a cross-over design, respectively [ 79 , 101 ]. Among the parallel RCTs, 27 featured two arms [ 48 , 57 , 67 - 73 , 76 , 78 , 81 , 83 - 85 , 88 - 93 , 95 , 96 , 99 , 102 - 104 ], while eight featured multiple intervention arms [ 49 , 77 , 82 , 86 , 87 , 94 , 97 , 98 ]. For instance, Finkelstein et al [ 82 ] conducted an RCT with four groups; three groups receiving a Fitbit device and the other receiving interventional components differing in terms of the type of financial incentives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies (35/37, 95%) were parallel RCTs, while two studies used a factorial design and a cross-over design, respectively [ 79 , 101 ]. Among the parallel RCTs, 27 featured two arms [ 48 , 57 , 67 - 73 , 76 , 78 , 81 , 83 - 85 , 88 - 93 , 95 , 96 , 99 , 102 - 104 ], while eight featured multiple intervention arms [ 49 , 77 , 82 , 86 , 87 , 94 , 97 , 98 ]. For instance, Finkelstein et al [ 82 ] conducted an RCT with four groups; three groups receiving a Fitbit device and the other receiving interventional components differing in terms of the type of financial incentives.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, there was a wide variety of Fitbit devices used in the included studies. Most of them (17/37, 46%) used clip-on devices such as Fitbit Zip [ 76 , 79 , 82 , 83 , 87 , 88 , 90 , 92 , 96 - 98 ], Fitbit One [ 48 , 68 , 81 , 84 , 94 ], and Fitbit Ultra [ 85 ]. Seven studies did not specify which model was used [ 49 , 67 , 69 , 70 , 95 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on two RCTs where patients at risk of foot ulceration participated in a training programme that increased their weight‐bearing activity, but where this did not result in increased incidence of ulceration, we suggest to consider advising people at low or moderate risk for ulceration (IWGDF 1 or 2) that a small increase in the level of weight‐bearing daily activities is likely to be safe. We define a small increase as 1000 steps/day, based on the increases seen in these two studies, and an RCT that showed such an increase to be beneficial for glycaemic control in people with diabetes . It is advisable to increase daily steps by a maximum of 10% per week, until a person reaches an overall increase of 1000 steps/day in comparison to baseline.…”
Section: Treating Risk Factors For Ulcerationmentioning
confidence: 99%